Effect of transglutaminase enzyme treatment on some rheological properties for the Iraqi wheat flour of Al-Rasheed class - Ramadhan, Hussein Jaafer; Nasir, Jassim M. (Journal of Kerbala for Agricultural Sciences, 2016)
The current study was undertaken to explore the possibility of improving chemical and rheological properties of Iraqi wheat flour dough (Al-Rasheed Class), by adding bacterial transglutaminase enzyme. The flour used currently was poor quality, as the development time and stability of the dough were low and the greatest viscosity was up from the normal limit of the flour suitable for the bread industry. The extension resistance, extensibility, extensograph area as well as the protein percentage was low. The flour treated with different concentrations of transglutaminase enzyme (10, 30, 50, 100 and 150 units /100 gm flour). Greater extension resistance, extensograph area and greatest resistance were obtained using 30 unit /100 gm flour transglutaminase as compared with the control and remaining treatment. Moreover, 50 unit/100 gm flour of transglutaminase revealed a significant increase in strong and dry gluten content. Flour treated with all transglutaminase concentration exhibited the significantly greater gluten index.